LGBT people's knowledge of and preparedness to discuss end‐of‐life care planning options. (17th June 2014) - Hughes, Mark; Cartwright, Colleen
Abstract Despite the devastating impact of HIV/AIDS, end‐of‐life care planning among lesbian, gay, bisexual and transgender (LGBT) communities is relatively under‐researched, especially in Australia. This paper reports findings of a survey of 305 LGBT people living in New South Wales, which examined their knowledge of and attitudes towards end‐of‐life care. The focus of this paper is their preparedness to discuss with healthcare providers any end‐of‐life care plans. The results highlight that while the majority of respondents were aware of three of the four key end‐of‐life care planning options available in New South Wales – enduring powers of attorney, enduring guardians and person responsible (only a minority had heard of advance healthcare directives) – a much smaller number of people had actually taken up these options. Only a minority of respondents were able to identify correctly who had the legal right to make treatment decisions for a person who is unconscious following a car accident. A small proportion of people had discussed end‐of‐life care options with general practitioners or another main healthcare provider, and only in very few cases were these issues raised by the practitioners themselves. Those most likely to not feel comfortable discussing these issues with practitioners included younger people, those not fully open about their sexuality to family members, and transgender people and others who do not define their gender as male or female. The paper highlights the importance of education strategies to raise awareness of the end‐of‐life care planning options among LGBT people, as well as strategies for increasing health providers' preparedness to discuss these issues with LGBT patients.